Potencjał mediacyjny spraw administracyjnych - Nasiadka, Łukasz (Studia Prawa Publicznego, 2024)
Mediation was introduced into general administrative proceedings by the Act of 7 April 2017 amending the Act - Code of Administrative Procedure and certain other acts, and was finally regulated in Chapter 5a of Section II of the CAP. At present, public administration bodies, in cases whose nature allows to do so, seek amicable settlements of disputed issues and aim to determine the rights and obligations which are the subject of the proceedings, in matters within their jurisdiction, in particular, by taking actions necessary for mediation. Mediation as a way of settling administrative law cases is not developing as dynamically in Polish practice as the legislator expected. One of the reasons for this state of affairs is the lack of a clear definition of the catalogue of cases in which mediation is possible and justified. At the same time, administrative mediation is not a legally unlimited construction. Its use has been limited by the legislator through prerequisites, i.e. legal requirements on which its legal admissibility depends. The key in this respect was to determine the prospects for concluding mediation in the mode specified in Article 96a § 3 of the CAP, i.e. by issuing a decision acceptable to the parties to the proceedings or concluding an administrative settlement. The study attempted to apply various criteria, such as the ways in which the proceedings were initiated, their subject matter, the state of progress of the investigation and the different categories of participants. On the basis of these, the ‘mediation potential’ of administrative cases was sought.